Against humanity : lessons from the Lord's Resistance Army - Dubal, Sam, 1986- (Oakland, California : University of California Press, 2018)
"This is not about crimes against humanity. Rather, it is an indictm ent of "humanity", the concept that lies at the heart of human rights a nd humanitarian missions. Based on fieldwork in northern Uganda, this b ook brings readers inside the Lord's Resistance Army, an insurgent grou p accused of rape, forced conscription of children, and inhumane acts o f violence. The author talks with and learns from former rebels as they find meaning in wartime violence, politics, spirituality, and love--ex periences that observers often place outside the boundaries of humanity . Rather than approaching the LRA as a set of possibilities, humanity l ooks at the LRA as a set of problems, as inhuman enemies needing reform . Humanity hegemonizes what counts as good in ways that are difficult t o question or challenge. It relies on very specific notions of the good --shaped in ideals of modern violence, technology, modernity, and reaso n, among others--in ways that do violence to the common good. What emer ges from this ethnography is an unorthodox question--what would it mean to be 'against humanity'? Against Humanity provocatively asks us how t o honor life existing outside normative moralities. It challenges us to shift toward alternative, more radical approaches to humanitarian, pol itical, medical, and other interventions, rooted in anti-humanism"--Pro vided by publisher.
Includes bibliographical references (pages 253-268) and index.
Keywords: Lord's Resistance Army; Humanity; Insurgency -- Uganda -- Case studies